Neoliberalism and management accounting: reconfiguring governmentality and extending territories. Issue 3 (18th February 2021) - Wickramasinghe, Danture; Cooper, Christine; Alawattage, Chandana
Abstract : Purpose: The purpose of this paper is to introduce the themes and aims of this Accounting, Auditing & Accountability ( AAAJ ) special issue and comments on the papers included in the issue. The paper provides a thematic outline along which the future researchers can undertake more empirical research examining how neoliberalism shapes, and shaped by, management accounting. Design/methodology/approach: This entails a brief review of the previous critical accounting works that refer to liberalism and neoliberalism to identify and highlight the specific themes and trajectories of neoliberal implications of management accounting has been and can be explored. This is followed by a brief commentary on the papers the authors have included in this special issue; these commentaries explain how these papers capture various dimensions of enabling and enacting neoliberal governmentality. Findings: The authors found that management accounting is now entering new territories beyond its conventional disciplinary enclosures of confinement, reconfiguring its functionalities to enable and enact a circulatory mode of neoliberal governmentality. These new functionalities then produce and reproduce entrepreneurial selves in myriad forms of social connections, networks and platforms within and beyond formal organizational settings, amid plethora of conducts, counter-conducts and resistances and new forms of identities and subjectivities. Research limitations/implications: This review can be read in relation to the papers included in the special issue as the whole issue will inspire more ideas, frameworks and methodologies for further studies. Originality/value: There is little research reviewing and commenting how management accounting now being enacted and enabled with new functionalities operating new territories and reconfiguring forms of governmentality. This paper inspires a new agenda on this project.